Stigma or reality: Efficiency of public companies? Analysis of peruvian and mexican cases - Farías Ruelas, Luz María (2019)
In the last two decades, has been implemented in Latin America results based management for public entities, searching to increase efficiency. The research has as purpose to identify for Peru and Mexico, the results of the direct impact in the efficiency of the application of public resources, seen from a direct increase in the goods and services offered to the citizens. Services as a direct procedures in government agencies, among others; goods, rights or subsidies, granted directly to the citizens: lighting, support programs for groups with extreme poverty, roads, among others. It will focus on myths and realities, political interests, and the presentation of a series of measures that could lead to the optimization of public companies; every time that, in other continents, it exist a direct benefit to the society by had efficient public companies. Even in Latin America, have been exist and exist companies that deny the popular saying for its profitability, understood as a direct benefit to the society; either through public revenues that are destinated to direct public goods and services in the cities, or by their quality and efficiency in the atention and tracing of the procedures entered by citizens. Perhaps the inefficiency of public entities does not establish a reality, but a fallacy built by entities interested in turnnig an incontrastable truth.